Britain, Ireland and the Second World War - Wood, Ian S. (Societies at war., 2010)
For Britain the Second World War exists in popular memory as a time of heroic sacrifice, survival and ultimate victory over Fascism. In the Irish state the years 1939-1945 are still remembered simply as 'the Emergency'. Eire was one of many small states which in 1939 chose not to stay out of the war but one of the few able to maintain its non-belligerency as a policy. How much this owed to Britain's military resolve or to the political skills of Ã⁹amon de Valera is a key question which this new book will explore. It will also examine the tensions Eire's policy created in its relations with Winston Churchill and with the United States. The author also explores propaganda, censorship and Irish state security and the degree to which it involves secret co-operation with Britain. Disturbing issues are also raised like the IRA's relationship to Nazi Germany and ambivalent Irish attitudes to the Holocaust. Drawing upon both published and unpublished sources, this book illustrates the war's impact on people on both sides of the border and shows how it failed to resolve sectarian problems in Northern Ireland while raising higher the barriers of misunderstanding between it and the Irish state across its border.